Epidemiological evidence and association of human papillomavirus with esophageal cancer in northeastern Thailand: a case–control study - Burassakarn, Ati; Pientong, Chamsai; Tongchai, Panwad; Wongjampa, Weerayut; Poosari, Arisara; Udomsin, Apiradee; Sa-ngiamwibool, Prakasit; Ungareewittaya, Piti; Nutravong, Thitima; Ekalaksananan, Tipaya (Frontiers in Microbiology, 2023)
Recently, epidemiological evidence of high-risk human papillomavirus (hrHPV) and its association with the increasing risk of esophageal cancer (EC) have been described. However, the involvement of such a virus in the pathogenesis of EC is still inconclusive in the literature. Therefore, our objective was to clarify the epidemiology of HPV infections in primarily diagnosed EC cases and validate this correlation with hospital-based control patients using a retrospective study with a case–control model. Here, we reported that the overall prevalence of HPV DNA was statistically associated with an increased risk of EC (OR, 3.3; 95% CI, 2.5–4.3). Interestingly, a history of gastroesophageal reflux disease (GERD) was constituted and significantly associated with HPV prevalence (adjusted OR, 4.6; 95% CI, 2.2–9.5). Furthermore, our meta-analysis in public databases also indicated that the combined OR and 95% CI between HPV infection and EC risk were 3.31 and 2.53–4.34, respectively, with significant heterogeneity (I2 = 78%). Variations in the geographic study, tissue type, and detection method remain potential predictors of heterogeneity. In addition, publication bias and sensitivity analysis were not observed, and the results exhibited stable outcomes. Collectively, we specify the recent epidemiological evidence in a validation of the distributed HPV, which might be statistically associated with an increased risk of EC. However, additional high-quality studies with larger sample sizes are needed to further verify the link between HPV and EC.